2010
DOI: 10.1007/s11738-010-0494-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide affecting root growth, lignification and related enzymes in soybean seedlings

Abstract: This study analyzed the involvement of nitric oxide (NO) in the root lignification of soybean seedlings. To this end, changes in root cell viability; phenylalanine ammonia-lyase (PAL) and soluble and cell wall bound peroxidase (POD) activities and lignin and hydrogen peroxide (H 2 O 2 ) contents of soybean roots treated with the NO-donor sodium nitroprusside (SNP) and its relationships with root growth were evaluated. Seedlings were cultivated in a nutrient solution supplemented with 5 to 1,000 lM SNP for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…The color of LRs in 10 µmol and 50 µmol SNP treated seedlings was white, while that of 100 µmol and 500 µmol SNP treated seedlings was brownish yellow and brown, respectively. These results indicate that apart from a signaling molecule, exogenous NO may act as a stress factor in controlling LR initiation and development, in agreement with recent findings in soybean seedlings (Böhm et al 2010).…”
Section: Resultssupporting
confidence: 92%
“…The color of LRs in 10 µmol and 50 µmol SNP treated seedlings was white, while that of 100 µmol and 500 µmol SNP treated seedlings was brownish yellow and brown, respectively. These results indicate that apart from a signaling molecule, exogenous NO may act as a stress factor in controlling LR initiation and development, in agreement with recent findings in soybean seedlings (Böhm et al 2010).…”
Section: Resultssupporting
confidence: 92%
“…It has also been evident that the effect of NO is in concentration-dependent manner. In soybean seedlings, a high concentration (1 mM) of SNP reduced reversely root growth and lignifications, and caused a loss of cell viability as a result (Böhm et al 2010). In wheat plants, as suggested by others research, high concentration of SNP (2 mM) inhibited wheat growth, aggravated the accumulation of hydrogen peroxide and lipid peroxidation, and even was considered as another stress factor (Tian and Lei 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Many previous studies have reported presence of NO in the plant kingdom and its involvement in growth, development, and defense responses (Böhm et al 2010;Beligni and Lamattina 1999). Exogenous NO donor could ameliorate the inhibition of wheat seed germination induced by drought stress (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…More specifically, NO plays important role in responses to abiotic stresses (including wounding, oxidative damage, heavy metal toxicity, drought, and salinity) as well as biotic stresses (Arasimowicz-Jelonek and FloryszakWieczorek 2007;Qiao and Fan 2008;Misra et al 2011;Siddiqui et al 2011). Depending on the concentration and site of action, NO could serve either as a cytoprotectant or a cytotoxin (Beligni and Lamattina 1999;Lamattina et al 2003;Böhm et al 2010). To date, several reports have signified cytoprotective roles of NO at low concentrations in promoting normal plant growth and development (Beligni and Lamattina 2001;Libourel et al 2006;Bethke et al 2007).…”
Section: Introductionmentioning
confidence: 99%